Pengaruh Akun Media Sosial Instagram @psdku.unpadpangandaran Terhadap Pemenuhan Kebutuhan Informasi Followers Calon Mahasiswa - Monica Dhelta Dwi Safitri; Ilham Gemiharto; Dwi Masrina (Lembaga Pengembangan Kinerja Dosen, 2025)
The ease of accessing social media makes individuals or agencies use social media as a tool to disseminate information. One of the institutions that utilize social media, especially Instagram, to disseminate information is PSDKU Padjadjaran University. The information submitted by PSDKU Padjadjaran University is related to academic and non-academic information. This study aims to measure how much influence the Instagram social media account @psdku.unpadpangandaran has on fulfilling the information needs of prospective student followers. The theoretical basis used in this study is the information search theory proposed by Wilson. This study uses a quantitative approach with a survey method. Where researchers distributed questionnaires to a research sample of 100 respondents who came from followers of the Instagram social media account @psdku.unpadpangandaran. The sampling of this study used non-probability sampling techniques, namely purposive sampling and using the slovin formula. The results of this study indicate that the variables of intensity, message content, and message attractiveness have a significant effect on fulfilling information needs. This is because all variables have a significance value smaller than 0.05. In addition, the three variables partially affect the fulfillment of the information needs of prospective student followers. It can be concluded that the Instagram social media account @psdku.unpadpangandaran can fulfill the information needs of prospective student followers.